CHAMELEON MECHANISM IN SCALAR-TENSOR GRAVITATION THEORY - Fahmi, Fathiyul
One of today’s cosmological problem is universe’s accelerated expansion. This phenomena can be explained by introducing a matter component called dark energy. Cosmological constans is usually identified as dark matter, but there is an alternative using quintessence scalar field. This scalar field is usually coupled with matter field so it gives birth to a fifth force and may cause a violation to equivalence principle. Experimental results on Earth and solar system gives a boundary to very small equivalence principle violation permitted, thus a screening mechanism to suppress the effect of fifth force is needed. One of the most studied screening mechanism is chameleon mechanism. In this mechanism, the effective potential of the scalar field is a function of local matter density, in a way so the mass of the scalar field is proportional to the local density matter. In this thesis, we examine chameleon mechanism on a theory covered in general scalar-tensor theory that is Horndeski theory.